Análisis de los principales mecanismos de cooperación internacional en el marco del posconflicto en Colombia, para la financiación de iniciativas productivas relacionadas con el desarrollo económico local (2019)
The research project was developed, identifying the institutional framework of international cooperation in Colombia to contextualize it locally and globally, conceiving in a timeline the evolution of the concept of "cooperation", until reaching shared responsibility and its impact on social cohesion, including institutionality around the issue and its relevance to Colombia given the role it has traditionally played in many social initiatives and recently, with the accompaniment of the peace process and the implementation of the Havana Agreements, within the framework of the post conflict Subsequently, the analysis of the existing international cooperation mechanisms was established, identifying the characteristics, regulations and areas of interest that define each mechanism. The analysis of the profiles of the projects is carried out from its implementation in the country, under the following eligibility and impact criteria: Local Economic Development (LED), sustainable rural development and peace building, elements that converge with those stipulated in the signature of peace agreements with the FARC, which are framed as a decisive element for the future of the country, thanks to the support of the agencies and resources of international cooperation.